Current progress in iPSC disease modeling - Birbrair, Alexander (Advances in stem cell biology ;, 2022)
Current Progress in iPSC Disease Modeling, Volume Fourteen in the Advances in Stem Cell Biology series, is a timely and expansive collection of information and new discoveries in the field. This new volume addresses advances in research on how induced pluripotent stem cells are used for the creation of new tissues and organs. The creation of iPSC technology allowed the development of disease-specific human pluripotent stem cells. These cells allow researchers to study questions once impossible for some human diseases. This volume addresses iPSCs for vascular tissue engineering, bioprinting, derived lung organoids for pulmonary disorders, skeletal muscle engineering, human kidney organoids, and more. It is written for researchers and scientists in stem cell therapy, cell biology, regenerative medicine and organ transplantation, and is contributed by world-renowned authors in the field.